THE ROLE OF SYNONYMY AND ANTONYMY PHENOMENA IN THE CHAIN OF GRADUAL RELATIONS - Umidjon Yigtaliyev; Shohruhbek Umidjonov (Zeta Repository, 2023)
This article explores the concept of a graduated chain of relations and the role of synonymy and antonymy phenomena in it using the example of Uzbek language sources.